Léonie - Adler, Elizabeth (Elizabeth A.) (New York : Dell Publishing, 1987)
When Leonie, a half-Egyptian, half-French country girl, moves to Paris she captures the lascivious attentions of the Duc de Courmont, who manipulates circumstances in a desperate attempt to quench his obsession for her.
National College of Business and Arts
Keywords: Love stories